Consumer behavior in short agrifood chains in the region of Corede Rio da Várzea/RS/Brazil - Nogueira, Carolina de Mattos; Fagundes, Paloma de Mattos (Revista de Administração da UFSM, 2021)
Purpose – To analyze consumer purchase intentions at open fairs in the region of Regional Development Council (COREDE) Rio da Várzea/Rio Grande do Sul in the light of the Theory of Planned Behavior and the influencing factors in the decision-making process. Design/methodology/approach - The scope of the research requires an analysis involving the interaction of TPB, the decision-making process and the factors that influence consumer behavior, making it possible, based on statistical inferences, to analyze multiple variables simultaneously through the use of the Modeling technique of Structural Equations. The questionnaire was applied to 195 consumers of open markets using the non-probabilistic convenience sampling technique. Findings – The model of causal relationships of the three beliefs and four influencing factors allowed testing whether the seven constructs are correlated. The correlation between all indicators was significant and positive and the model that obtained greater significance was the construct model referring to Personal Factors. In this model, the concern with health and quality of life were the most relevant variables, allowing us to conclude that the search for a healthy life makes consumers worry about looking for natural foods, which are found in open markets. Originality/value – Studies that address this entire context have not been carried out in the region of the COREDE Rio da Várzea.